Pro and Cons of Transurethral Self-Catheterization in Boys: A Long-Term Teaching Experience in a Pediatric Rehabilitation Centre - Faure, Alice; Peycelon, Matthieu; Lallemant, Pauline; Audry, Georges; Forin, Veronique (Urology Journal, 2016)
Purpose: To describe the acceptance and efficacy of clean intermittent catheterization (CIC) in the management of lower urinary tract (LUT) dysfunction regardless of the age of the children and their degree of urethral sensation. Materials and Methods: We retrospectively evaluated boys managed with CIC at a pediatric teaching hospital between 1992 and 2014. Age, urethral sensation, acceptance, efficacy in terms of continence and preserving upper urinary tract and genitourinary complications were reviewed in the medical records. Results: Sixty boys managed with CIC for LUT dysfunction due to neurological or urological disorders were identified. The median age at CIC initiation was 8.2 years (range, 1.4-18). With regard to age, CIC was well tolerated in younger boys and without genital sensation. Failure in the CIC protocol occurred within the first six months (n = 9). More boys with genital sensation were socially continent with CIC (91% versus 83%, P = .05). Vesicoureteral reflux was resolved in 69% of boys (P = .03), and hydronephrosis in 54% (P = .07). Conclusion: CIC was effective in terms of continence and renal protection. The procedure was feasible even in boys with preserved urethral sensation. Therapeutic education by a dedicated urotherapy nurse is the key factor in ensuring long-term CIC compliance and acceptability.